IMPLEMENTASI SISTEM JAMINAN HALAL PRODUK LIVIA CATERING BERDASARKAN HAS 23000 - Khairunnisa Indah Safitri; Ika Dyah Kumalasari (Prodi Teknologi Pangan Fakultas Pertanian Universitas Islam Indragiri, 2022)
The implementation of HAS 23000 is a requirement of LPPOM MUI to obtain a halalcertificate.Thepurposeoftheimplementationofpracticalworkistodeterminetheimplementation of the halal assurance system based on the has 23000 standard criteria andto find out that products and raw materials have received halal approval by the MUI. Themethodsusedindatacollectionareobservationmethods,interviews,directpractice,documentation, and literature studies. The results obtained after being carried out related totheimplementationofthehalalassurancesystemat LiviaCateringthereareshortcomingsinthe halal assurance system criteria from the halal management team, internal audits, andmanagement reviews.